TINJAUAN YURIDIS PEMBERIAN GRASI TERHADAP PELAKU TINDAK PIDANA KORUPSI DIKAITKAN DENGAN TEORI PEMIDANAAN - Karefna, Ditya; R, Mukhlis; Ferawati, Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Clemency is a pardon in the form of amendment, mitigation, reduction, or elimination of the implementation of a criminal offense given by the president. Granting clemency to prisoners is regulated in the Indonesian constitution, namely Article 14 Paragraph (1) of the Constitution of the Republic of Indonesia that, "The President grants clemency and rehabilitation by taking into account the considerations of the Supreme Court". Clemency is a reduction of punishment, this can be found in Indonesian positive law, namely in Article 1 of Law No. 22 of 2002 in conjunction with Law No. 5 of 2010 concerning clemency.This research will be compiled using the juridical normative type of research, which is research that is focused on examining the application of the rules or norms in positive law. The approach used in this research is to use a normative approach, namely literature law research. The results of the research conducted by the author are, first to find out whether or not clemency is granted to the perpetrator of the criminal act of corruption if it is linked to the theory of punishment and the ideal arrangement related to clemency against corruptors.The granting of clemency by the President has a negative impact on the convicted person, that is, it does not cause a deterrent effect, because with the provision of clemency, the convict can repeat the same crime. The impact on society with the provision of clemency in certain cases is that it is feared that the public will commit the same crime, because it is felt that it does not provide a deterrent effect for criminals, especially those who commit corruption. Granting clemency to perpetrators of criminal acts of corruption will have a negative impact on efforts to eradicate corruption. Clemency granting must also be tightened so that there is a deterrent effect in the future for corruptors. Because the party most affected by corruption crimes committed by convicted people is the community itself. Therefore, it is necessary to have a criminal law policy against the granting of clemency for criminal acts of corruption so that clemency is not given to convicts caught in corruption cases.Keywords: Granting Clemency- Corruption Crime - Criminal Theory